(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
Now, practically in the all territory of the Russian Federation and, in particular, in it’s Northwest federal region we can say about The Russian Renaissance with strongly pronounced elements of eclecticism. It’s no coincidence, as the nature-innovative potential forces to think about investment many means on development of the real estate and tourist-recreational zones as a whole. Answering repeating questions, where are the most dangerous areas for an investment of means and for the business organization, in particular, in St.-Petersburg, even more often you are surprised to such questions, understanding that danger can proceed, first of all, from a geoecological situation on cities territories. We don’t have reservations and/or divisions of administrative areas by a principle poor/rich and/or our and another's areas. You can feel genuine pride from comprehension of our deep tolerance. Means, it was possible to accept all the best, to learn to understand associates, to appreciate friendly relations, to live, without giving in to minute tendencies and the imposed stereotypes introduced by market relations.